2019
DOI: 10.1016/j.eurox.2019.100072
|View full text |Cite
|
Sign up to set email alerts
|

Use of antenatal fluorinated corticosteroids in management of congenital heart block: Systematic review and meta-analysis

Abstract: Objective To evaluate outcomes of fluorinated corticosteroids, with or without other medications, for treatment of congenital heart block in-utero. Study design A search was conducted through MEDLINE, EMBASE, WEB OF SCIENCE and SCOPUS from inception to October 2017. Only comparative studies are considered eligible. Outcomes include fetal death, downgrade of heart block, neonatal death, need for neonatal pacing, fetal and maternal complications. Random effects model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 54 publications
(70 reference statements)
0
24
0
Order By: Relevance
“…Theoretically, FS would interfere with this evolution. In practice however, studies have repeatedly shown that FS are not efficacious in preventing CHB or evolution to complete AV block [21,22]. Moreover, their use is associated with important adverse effects both for the woman and the baby including impaired kidney function with reduced amniotic fluid volume, impaired thyroid function in the fetus, low birth weight, maternal glucose intolerance, anxiety [23,24] and possible negative effects on brain development of the child [24].…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, FS would interfere with this evolution. In practice however, studies have repeatedly shown that FS are not efficacious in preventing CHB or evolution to complete AV block [21,22]. Moreover, their use is associated with important adverse effects both for the woman and the baby including impaired kidney function with reduced amniotic fluid volume, impaired thyroid function in the fetus, low birth weight, maternal glucose intolerance, anxiety [23,24] and possible negative effects on brain development of the child [24].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis [ 76 ], fluorinated glucocorticoids did not improve fetal or neonatal survival, while prolonged administration of fluorinated glucocorticoids was associated with fetal and maternal complications. However, this meta-analysis is difficult to interpret.…”
Section: Bradyarrhythmiasmentioning
confidence: 99%
“…13 A recent report from Izmirly et al, 14 involving 54 CAVB in fetuses of anti-SSA/Ropositive mothers, highlighted that hydroxychloroquine significantly reduces the recurrence of CAVB below the historical rate by >50%. As for steroids, in two meta-analyses from Ciardulli et al 15 and Michael et al 16 antenatal maternal corticosteroids failed to improve neonatal morbidity and mortality related to congenital AVB and might be associated with a higher incidence of fetal and maternal complications. A treatment including transplacental dexamethasone fetal administration of and beta-stimulation when the heart rate falls below 55 bpm, has been demonstrated to reduce morbidity and improved the outcome of isolated fetal CAVB.…”
Section: Congenital Atrioventricular Blockmentioning
confidence: 99%